Lung Secretoglobin Scgb1a1 Influences Alveolar Macrophage-Mediated Inflammation and Immunity - Xu, Min; Yang, Wei; Wang, Xuanchuan; Nayak, Deepak Kumar (Frontiers in Immunology, 2020)
Alveolar macrophage (AM) is a mononuclear phagocyte key to the defense against respiratory infections. To understand AM’s role in airway disease development, we examined the influence of Secretoglobin family 1a member 1 (SCGB1A1), a pulmonary surfactant protein, on AM development and function. In a murine model, high-throughput RNA-sequencing and gene expression analyses were performed on purified AMs isolated from mice lacking in Scgb1a1 gene and were compared with that from mice expressing the wild type Scgb1a1 at weaning (4 week), puberty (8 week), early adult (12 week), and middle age (40 week). AMs from early adult mice under Scgb1a1 sufficiency demonstrated a total of 37 up-regulated biological pathways compared to that at weaning, from which 30 were directly involved with antigen presentation, anti-viral immunity and inflammation. Importantly, these pathways under Scgb1a1 deficiency were significantly down-regulated compared to that in the age-matched Scgb1a1-sufficient counterparts. Furthermore, AMs from Scgb1a1-deficient mice showed an early activation of inflammatory pathways compared with that from Scgb1a1-sufficient mice. Our in vitro experiments with AM culture established that exogenous supplementation of SCGB1a1 protein significantly reduced AM responses to microbial stimuli where SCGB1a1 was effective in blunting the release of cytokines and chemokines (including IL-1b, IL-6, IL-8, MIP-1a, TNF-a, and MCP-1). Taken together, these findings suggest an important role for Scgb1a1 in shaping the AM-mediated inflammation and immune responses, and in mitigating cytokine surges in the lungs.